ICDS Scheme to the Growth Development in Preschoolers: A Systematic Review of Literature - Jemy Elizabeth Joseph (Intelektual Pustaka Media Utama, 2014)
The health scenario in our country is rapidly changing, both in terms of the public health challenges that we face as well as our response to these challenges. As India becomes more and more developed and we have greater means at our disposal, our response to our health challenges must reflect our changing health and socio-economic status. India faces enormous challenges in the area of women’s and children’s health. These findings point to the importance of investing in various growth factors and sanitation, and educating the public about hygiene to promote health knowledge and better child outcomes. As importantly, such investments have the potential of making the feeding program more effective. ICDS therefore takes holistic view of the development of the child and attempts to improve both his/her prenatal and postnatal environment. Accordingly, besides children in their formative years (0-6 years), women between 15 to 45 years are also covered by the programme as these are child bearing years in the life of a women and her nutrition and health status has a bearing on the development of the child.